Analysis of Colombian Valuation Techniques for The Palafitic Housing of The Pacific. The Case of Buenaventura, Valle del Cauca - Bermudez Ayala, Maria Alejandra; Castro Ortiz, Juan Camilo; Avendaño Arias, Johan Andrés (Sociedad y Economía, 2021)
This article presents a reflexive analysis of the Colombian valuation procedures in the context of the palafitic housing in the Pacific region, specifically in the municipality of Buenaventura, Valle del Cauca. The territorial development from the first representative establishments in the region to the progress and persistence of the traditional architectural typologies, as well as the most significant characteristics of the current structure of pile dwellings are approached. The current valuation regulations were contrasted for an approach to the methods according to this typology; as a first approximation, the replacement cost and rental capitalization methods make it possible to assign an economic value to the traditional housing of the Pacific. However, it is necessary to confront the challenge of considering this constructive structure in a lawful way, as well as to consider the cultural value present in the architectural design as a response to the patrimonial valuation that it represents for the region in general.